Protoporphyrin IX plasma and blood pharmacokinetics and brain tumor distribution determined by a validated LC–MS/MS method - William Knight; Tigran Margaryan; Kamal Shaik; Nader Sanai; Artak Tovmasyan (Scientific Reports)
Abstract Protoporphyrin IX (PPIX) is a fluorescent metabolite in the heme biosynthesis pathway, and cancer cells accumulate it when 5-aminolevulinic acid (5-ALA), a precursor, is administered. In the U.S., 5-ALA is approved for visualizing high-grade gliomas (HGG) during fluorescence-guided surgery. PPIX is also central to experimental photodynamic and sonodynamic therapies for HGG. Additionally, PPIX measurement is critical for diagnosing and monitoring porphyrias. Despite the need for a sensitive and rapid bioanalytical method for accurate quantification of PPIX in biospecimens, no reliable validation of an LC–MS/MS method is available due to challenges related to its chemical instability, poor solubility, and tendency to aggregate. This work is the first to present a fully validated, sensitive, and rapid LC–MS/MS method for determining PPIX levels in human plasma, blood, and brain tumors. The method overcomes stability concerns, achieving a 3.5-min total run-time with a concentration range of 1–2000 nmol/L for plasma and tumors, and 10–2000 nmol/L for blood. Application of the method in a clinical trial, which assesses sonodynamic therapy for HGG patients, shows significant PPIX production, peaking in plasma and blood six hours post-5-ALA administration. In recurrent HGG patients, PPIX levels were notably higher in gadolinium-enhancing tumor regions compared to non-enhancing areas, indicating preferential accumulation in tumors.